SISTEM PENGUKURAN INVESTASI TEKNOLOGI INFORMASI PT. SOUTH PACIFIC VISCOSE PURWAKARTA MENGGUNAKAN VAL IT - Adi Lukman; Wina Witanti; Wisnu Uriawan (PROCEEDING STIMA)
Currently, lot of organization which depend transactions largely and smooth business to information technology sector. Much organization predicted about how big the benefits actually from information technology sector if compared with investation. Others opinion affirm that evaluation of information technology results is essential with main challenges are adversity on measure of the effectiveness resulting system. The effectiveness in information technology covered not only that, but all component which establish system. Quality viewed as a value about a product perfection (including service) overall.Keywords: Investment management, Portfolio management, VAL IT, Value governance, information technology